STUDIES ON THE BIOCHEMICAL COMPOSITION Of .SOME FRESHWATER fiSHES Ill. OVARY - JAFRI, A. K.; QASIM, S. Z. (Fishery Technology, 1966)
Biochemical composition of the spent overies of 23 different species of freshwater fishes showed a much lower value for protein and fat with a much higher moistur(’ content than those of the ripe eggs, suggesting an inverse relationship between fat and moisture. Ovaries during the recovering phase showed fairly high values of phosphorus, but lower than those for the ripe eggs. Higher values of calcium and iron in spent ovaries than those in ripe eggs probably suggest that there is a greater requirement of calcium and iron during the spent phase of the gonads.